Advances in the management of primary and secondary insomnia - McCall, William Vaughn (Future Medicine Ltd (Unitec House, 2 Albert Place, London N3 1QB, UK), 2014)
These six chapters provide an overview on the causes, consequences and treatment of insomnia, and awareness of these issues will hopefully promote health and access to effective care for those suffering with primary or comorbid insomnia.